Evaluating the Surface Properties of Prosthodontic Polymer Impression Materials - Asmaa Abdeewi,; Gazia Elbakosh,; Milad Elshah,; Abdalbri Rhab,; Nasib Inwidah,; Samah Abu iemayd,; Areej Akhmaaj, (AlQalam Journal of Medical and Applied Sciences, 2024)
Surface properties of prosthodontic polymer impression materials, such as hardness, roughness, and accuracy, are crucial for the accurate replication of oral structures in restorative dentistry. To evaluate the surface properties by using different types of polymer impression materials commonly used in dentistry and analyze their surface characteristics. Materials and methods: Forty -five samples of materials were used, including alginate (irreversible hydrocolloid), condensation silicone (putty) and addition silicone (putty), study was conducted at the advanced medical polymer group in the Libyan Polymer Research Center to evaluate the surface properties of prosthodontic polymer impression materials. Three evaluation methods were used: Shore hardness testing, surface roughness testing, and dimensional accuracy measurements. Data analysis included mean, standard deviation, and One-way ANOVA calculations. Alginate has a lower hardness compared to addition silicone (putty) and condensation silicone (putty). The ANOVA test for surface roughness showed no significant differences among the materials, with a p-value of 0.027. For shore hardness, there were no significant differences among the materials, with a p-value of 0.000. The ANOVA test for dimensional accuracy showed no significant differences among the different periods for alginate, condensation silicone (putty) and addition silicone (putty), with p-values of 0.000 respectively. The study concluded that alginate had the lowest hardness and roughness compared to condensation silicone (putty) and addition silicone (putty). There are no significant differences among the material surface properties (Shore hardness and surface roughness) but not in dimensional accuracy among the materials. This information provides valuable insights for dental professionals working with impression material. تعتبر الخصائص السطحية لمواد طباعة البوليمر للتعويضات السنية، مثل الصلابة والخشونة والدقة، ضرورية للتكرار الدقيق للأنسجة والتركيبات الفموية في طب الأسنان الترميمية. الهدف من الدراسة هو تقييم خصائص السطح باستخدام أنواع مختلفة من مواد الطباعة البوليمرية شائعة الاستخدام في طب الأسنان وتحليل خصائص سطحها. تم استخدام خمسة وأربعين عينة من المواد، بما في ذلك الألجينات (غرواني مائي غير قابل للانعكاس)، سيليكون التكثيف (المعجون)، والسيليكون الإضافي (المعجون)، أجريت الدراسة في مجموعة البوليمرات الطبية المتقدمة في مركز أبحاث البوليمرات الليبي. لتقييم مدى فعالية الخصائص السطحية لمواد طبع البوليمر للتعويضات السنية. تم استخدام ثلاث طرق للتقييم: اختبار الصلابة، اختبار خشونة السطح، وايضا اختبار قياسات دقة الأبعاد. وشمل تحليل البيانات المتوسط والانحراف المعياري وحسابات ANOVA أحادية الاتجاه. الألجينات لديها صلابة أقل مقارنة بالسيليكون الإضافي (المعجون) وسيليكون التكثيف (المعجون). أظهر اختبار ANOVA لخشونة السطح عدم وجود فروق ذات دلالة إحصائية بين المواد، بقيمة p تبلغ 0.027. بالنسبة لصلابة، لم تكن هناك فروق ذات دلالة إحصائية بين المواد، بقيمة p 0.000. أظهر اختبار ANOVA لدقة الأبعاد عدم وجود فروق ذات دلالة إحصائية بين الفترات المختلفة للألجينات وسيليكون التكثيف (المعجون) والسيليكون الإضافي (المعجون)، مع قيم p تبلغ 0.000 على التوالي. خلصت الدراسة إلى أن الألجينات كان لديه أقل صلابة وخشونة مقارنة بسيليكون التكثيف (المعجون) وسيليكون الإضافة (المعجون). لا توجد فروق معنوية بين خواص سطح المادة (صلابة وخشونة السطح) ولكن ليس في دقة الأبعاد بين المواد. وتوفر هذه المعلومات رؤى قيمة للعاملين في طب الأسنان والاطباء الذين يعملون مع مواد الطبعات السنية